Anandamide Reduces the Toxic Synergism Exerted by Quinolinic Acid and Glutaric Acid in Rat Brain Neuronal Cells. (1st March 2019) - Kotlar, Ilan; Rangel-López, Edgar; Colonnello, Aline; Aguilera-Portillo, Gabriela; Serratos, Iris N.; Galván-Arzate, Sonia; Pedraza-Chaverri, José; Túnez, Isaac; Wajner, Moacir; Santamaría, Abel
Graphical abstract: Highlights: Quinolinate and Glutaric acid exert a toxic synergism in neuronal cells. The toxic model was tested in rat cultured neurons and cortical slices. The cannabinoid anandamide prevented toxic endpoints of synergism. Anandamide protection involved the partial participation of CB1 receptors. Novel mechanisms involved in Glutaric Acidemia type I are suggested. Abstract: The endocannabinoid system (ECS) regulates several physiological processes in the Central Nervous System, including the modulation of neuronal excitability via activation of cannabinoid receptors (CBr). Both glutaric acid (GA) and quinolinic acid (QUIN) are endogenous metabolites that, under pathological conditions, recruit common toxic mechanisms. A synergistic effect between them has already been demonstrated, supporting potential implications for glutaric acidemia type I (GA I). Here we investigated the possible involvement of a cannabinoid component in the toxic model exerted by QUIN + GA in rat cortical slices and primary neuronal cell cultures. The effects of the CB1 receptor agonist anandamide (AEA), and the fatty acid amide hydrolase inhibitor URB597, were tested on cell viability in cortical brain slices and primary neuronal cultures exposed to QUIN, GA, or QUIN + GA. As a pre-treatment to the QUIN + GA condition, AEA prevented the loss of cell viability in both preparations. URB597 only protected in a moderate manner the cultured neuronal cells against the QUIN + GA-induced damage. The use of the CB1 receptor reverse agonist AM251 in both biological preparations prevented partially the protective effects exerted by AEA, thus suggesting a partial role of CB1 receptors in this toxic model. AEA also prevented the cell damage and apoptotic death induced by the synergic model in cell cultures. Altogether, these findings demonstrate a modulatory role of the ECS on the synergic toxic actions exerted by QUIN + GA, thus providing key information for the understanding of the pathophysiological events occurring in GA I.